Demand for child health in Peru: an empirical and theoretical analysis - Cortez, Rafael (Universidad del Pacífico, 1995)
The author delves into the factors influencing health services demand. An empirical analysis was conducted based on regression models with dichotomous variables on a sample group of 4,540 children.   The main questions the piece attempts to answer are: Which are the factors behind the frequency of child illness in Peru and the household leader's decision to seek the assistance of medical services?; and what dictates the decision to visit a specific health center.